2019
DOI: 10.1175/jcli-d-18-0211.1
|View full text |Cite
|
Sign up to set email alerts
|

The Consistency of MJO Teleconnection Patterns: An Explanation Using Linear Rossby Wave Theory

Abstract: The Madden–Julian oscillation (MJO) excites strong variations in extratropical atmospheric circulations that have important implications for subseasonal-to-seasonal (S2S) prediction. A previous study showed that particular MJO phases are characterized by a consistent modulation of geopotential heights in the North Pacific and adjacent regions across different MJO events, and demonstrated that this consistency is beneficial for extended numerical weather forecasts (i.e., lead times of two weeks to one month). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 35 publications
5
62
0
Order By: Relevance
“…Similar results have been reported by Zhou and Miller (2005), Cassou (2008), L'Heureux and Higgins (2008), Mori and Watanabe (2008), Watanabe (2008), and Franzke et al (2011). Tseng et al (2019) show that PNA-like teleconnection patterns occur preferentially during particular MJO phases, due to diabatic heating anomalies in certain locations and the presence of Rossby-wave source dipoles. The presence of Rossby-wave source anomalies on either side of the subtropical jet stream can enhance the strength of PNA-like teleconnection patterns.…”
Section: An Overviewsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results have been reported by Zhou and Miller (2005), Cassou (2008), L'Heureux and Higgins (2008), Mori and Watanabe (2008), Watanabe (2008), and Franzke et al (2011). Tseng et al (2019) show that PNA-like teleconnection patterns occur preferentially during particular MJO phases, due to diabatic heating anomalies in certain locations and the presence of Rossby-wave source dipoles. The presence of Rossby-wave source anomalies on either side of the subtropical jet stream can enhance the strength of PNA-like teleconnection patterns.…”
Section: An Overviewsupporting
confidence: 87%
“…Tseng et al . () show that PNA‐like teleconnection patterns occur preferentially during particular MJO phases, due to diabatic heating anomalies in certain locations and the presence of Rossby‐wave source dipoles. The presence of Rossby‐wave source anomalies on either side of the subtropical jet stream can enhance the strength of PNA‐like teleconnection patterns.…”
Section: Extratropical Responsementioning
confidence: 97%
“…Days 290 8-18 are chosen based on previous research on MJO teleconnection timescales (e.g. Cassou 2008;Henderson et al 2016;Tseng et al 2019), however, these results are insensitive to variations of +/-5 days. Figure 8 shows the average prediction skill across leads 8-18 days for EQBO in orange (Figure 8a,b) and WQBO in teal (Figure 8c,d) along with average STRIPES values in black for all longitudes.…”
Section: Summary Of Northern Hemisphere Prediction Skillmentioning
confidence: 99%
“…The MJO is the dominant mode of intraseasonal variability in the tropics (Madden and Julian, 1971;Adames and Kim, 2016), and through its convective heating, modulates midlatitude weather, days to weeks after an MJO event (e.g. Vecchi 2004;Zhou et al 2012;Henderson et al 2016;Tseng et al 2019). Recent research has shown that the QBO impacts MJO amplitude, propagation, and prediction skill (Son et al, 2017;Nishimoto and Yoden, 2017;Zhang and Zhang, 2018;Marshall et al, 2017;Lim et al, 2019) as well as modulates MJO teleconnections (e.g.…”
Section: Summary Of Northern Hemisphere Prediction Skillmentioning
confidence: 99%
“…Rossby gyres flank its convective response, extending into the subtropics (Kiladis et al, ). Rossby waves also emanate poleward from the convective anomaly within the Indo‐Pacific warm pool, generating a Rossby wave train across the northern Pacific and into North America (Henderson et al, ; Seo & Lee, ; Tseng et al, ). Additional midlatitude linkages have been documented in the Southern Hemisphere, wherein the rainfall of Australia, subtropical South America, and Africa can be modulated by the MJO (Alvarez et al, ; Pohl et al, ; Wheeler et al, ).…”
Section: Introductionmentioning
confidence: 99%